2018
DOI: 10.1177/1077801218809942
|View full text |Cite
|
Sign up to set email alerts
|

People of Diverse Genders and/or Sexualities Caring For and Protecting Animal Companions in the Context of Domestic Violence

Abstract: + 61 88201 2491 ACKNOWLEDGEMENTS The first, second and fifth authors would like to acknowledge that they live and work on the lands of the Kaurna people, and to acknowledge their sovereignty as First Nations people. The fourth author would like to acknowledge the sovereignty of the Darumbal people, upon whose land she lives and works. KEYWORDS Gender and sexuality diversity; lesbian, gay, bisexual, transgender, queer family violence; animal companions. ABSTRACT This paper reports on a thematic analysis of open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 45 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…For example, one survey participant described the benefit of shared physical activity: 'The dog was a great comfort to me, I used to walk him and being together really helped.' While this is something that again has been reflected in previous research, both on animal and human companionship and how they mitigate the negative effects of DVA (Crane and Constantino, 2003;Taylor et al, 2018), it highlights the importance of attending to the animals providing support to transgender and non-binary people specifically.…”
Section: '[My] Trigger To Seek Help Was Seeing Animals Harmed': Animamentioning
confidence: 74%
See 3 more Smart Citations
“…For example, one survey participant described the benefit of shared physical activity: 'The dog was a great comfort to me, I used to walk him and being together really helped.' While this is something that again has been reflected in previous research, both on animal and human companionship and how they mitigate the negative effects of DVA (Crane and Constantino, 2003;Taylor et al, 2018), it highlights the importance of attending to the animals providing support to transgender and non-binary people specifically.…”
Section: '[My] Trigger To Seek Help Was Seeing Animals Harmed': Animamentioning
confidence: 74%
“…For example, we have found that experiencing close relationships with animal companions to a degree mitigates experiences of intimate partner DVA by helping to foster a greater sense of broader community connection and thus reducing psychological distress, and that this is especially true for TNB people (Riggs et al, 2018, 2019). Other findings (Taylor et al, 2018) suggest that TNB people’s experiences of family-based DVA may be offset by a desire to protect animals from harm, giving some people the strength to leave violent or abusive family situations.…”
Section: Background Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Sexuality and gender diverse groups are also likely to be marginalised, with many forming multi-species family arrangements. For instance, Taylor, Riggs, Donovan, Signal, and Fraser (2019) conducted a study of experiences of violence against humans and their companion animals among 503 people of diverse genders and sexualities living in either Australia or the United Kingdom. Findings revealed that those most marginalised in terms of gender or sexuality were also those most vulnerable to abuse, particularly identity-related abuse from family members (e.g., threatening to 'out' someone, withhold their medications, using wrong pronouns and so on).…”
Section: Theoretical Researchmentioning
confidence: 99%